A Tryptoline Ring‐Distortion Strategy Leads to Complex and Diverse Biologically Active Molecules from the Indole Alkaloid Yohimbine. Issue 18 (3rd February 2017) - Paciaroni, Nicholas G.; Ratnayake, Ranjala; Matthews, James H.; Norwood, Verrill M.; Arnold, Austin C.; Dang, Long H.; Luesch, Hendrik; Huigens, Robert W.
Abstract: High‐throughput screening (HTS) is the primary driver to current drug‐discovery efforts. New therapeutic agents that enter the market are a direct reflection of the structurally simple compounds that make up screening libraries. Unlike medically relevant natural products (e.g., morphine), small molecules currently being screened have a low fraction of sp 3 character and few, if any, stereogenic centers. Although simple compounds have been useful in drugging certain biological targets (e.g., protein kinases), more sophisticated targets (e.g., transcription factors) have largely evaded the discovery of new clinical agents from screening collections. Herein, a tryptoline ring‐distortion strategy is described that enables the rapid synthesis of 70 complex and diverse compounds from yohimbine (1 ); an indole alkaloid. The compounds that were synthesized had architecturally complex and unique scaffolds, unlike1 and other scaffolds. These compounds were subjected to phenotypic screens and reporter gene assays, leading to the identification of new compounds that possessed various biological activities, including antiproliferative activities against cancer cells with functional hypoxia‐inducible factors, nitric oxide inhibition, and inhibition and activation of the antioxidant response element. This tryptoline ring‐distortion strategy can begin to address diversity problems in screening libraries, while occupying biologically relevant chemical space in areas critical to human health. Abstract : Generating diversity : A tryptoline ring‐distortion strategy is described that enables the rapid synthesis of 70 complex and diverse compounds from yohimbine; an indole alkaloid. The compounds synthesized had architecturally complex and unique scaffolds, unlike that of yohimbine and other scaffolds.